THE INCLUSION OF THE DOCTOR IN THE TRAINING OF THE INTERPRETER IN HEALTHCARE - Sanz-Moreno, Raquel (2017)
The didactic experience we describe in this article aims at the acquisition and development of interpreting skills through four theoretical and practical sessions on Public Service Interpreting (PSI). This course is particular given that a healthcare professional takes part in the learning process, which is perfected with role-play exercises as a useful tool. The generous, active, and participative collaboration of these professionals had an influence both in the election of the cases analyzed in class—which were based on their own experiences with foreign patients—and in the assumption of their own professional roles in the dramatization exercises with students. The interaction with the doctors contributed to providing more realism and authenticity to the role-play activity and also facilitated the development of thematic, interpersonal, and strategic skills in students.